Rugby players’ satisfaction with custom-fitted mouthguards made with different materials - Brionnet JM, Roger-Leroi V, Tubert-Jeannin S, Garson A (Blackwell Synergy, 2001)
This study compared the comfort of two bimaxillary custom- fitted mouthguards. One type was made with silicone rubber and the other with methyl-methacrylate (acrylic).